A New Recursive Two Dimensional Pattern On Kolakoski Sequence - Rani, N Jansi; Vigneswaran, L; Dare, VR (International Journal of Computer Sciences and Engineering, 2025)
An efficient infinite Kolakoski sequence that’s not even in any particular order can be generated in two dimensional [2D] array of size (3x3) over a binary alphabet is introduced and it is denoted by -blocks, – positions, - rd column). In this paper first 66 blocks with 100 positions from Kolakoski sequence is considered and 2D arrays are analyzed. Also combinatorial properties of the basis arrays are studied